Watermarking for combating deepfakes - Li, Rui (Nanyang Technological University, 2023)
Over the recent years, great concerns have been aroused around the topic of Deefake due to its amazing ability in making a forgery image look like a genuine one. Many approaches have been developed to alleviate such risks. Among these, one noticeable track is to apply the model’s adversarial noise as a watermark to the image so that when the image is modified, it would be drastically distorted to the extent that the person’s facial features are no longer recognizable. Recent works have successfully developed a cross-model universal attack method that can produce a watermark that can protect multiple images against multiple models, breaking the previous constraint of watermarks being image-model-specific. However, to ensure the desired level of distortion, the adversarial noise threshold is set to relatively high, which makes the watermark ultimately visible on human faces, impairing the image quality and aesthetic. To mitigate this issue, we bring the idea of just noticeable difference (JND) into the cross-model universal attack method, intending to produce an image quality preserved universal watermark, while still maintaining the original protection performance. To achieve this, we have made several attempts. First, we replace the threshold clamp at each attacking step with the JND clamp. Second, we introduce a face parsing model to gain finer control over the JND values. Specifically, we use the face parsing model to segment portrait images into different parts and add scaling factors respectively for each part to scale the JND values. Through this, we are able to achieve good visual quality and at the same time, maintain good protection performance. Experiments are conducted to show that the watermark produced from the new JND cross-model universal watermark outperforms the previous one both in visual quality and protection performance.